2000
DOI: 10.1590/s0100-40422000000400005
|View full text |Cite
|
Sign up to set email alerts
|

Complexação da tetraciclina, da oxitetraciclina e da clortetraciclina com o catião cobre (II). Estudo potenciométrico

Abstract: Recebido em 20/4/99; aceito em 17/11/99 TETRACYCLINE, OXYTETRACYCLINE AND CHLORTETRACYCLINE COMPLEXATION WITH COPPER (II). POTENTIOMETRIC STUDY. Stability constants of complexes formed by copper (II) with three different tetracyclines (tetracycline, oxytetracycline and chlortetracycline)have been determined potentiometrically with an automatic system in aqueous medium at 25,0 ± 0,2 o C and I = 0,1 mol L -1 NaNO 3 . The protonation constants of the three tetracyclines were also determined under the same conditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 11 publications
0
2
0
1
Order By: Relevance
“…al., 2005;Duarte et al, 1999). It is important to know the interactions between OTC and metals, as this knowledge helps us to understand specific physiological mechanisms, and thus design more effective and rapid assays that can favorably compete with the official analytical methods (Pereira-Maia et al, 2010;Couto et al, 2000).…”
Section: Tetracyclinementioning
confidence: 99%
“…al., 2005;Duarte et al, 1999). It is important to know the interactions between OTC and metals, as this knowledge helps us to understand specific physiological mechanisms, and thus design more effective and rapid assays that can favorably compete with the official analytical methods (Pereira-Maia et al, 2010;Couto et al, 2000).…”
Section: Tetracyclinementioning
confidence: 99%
“…A further increase in the Cu/TC and Al/TC molar ratio caused a slight decrease of TC adsorption in the Cu 2+ system but a significant decrease in the Al 3+ system. The formation of other Cu-TC species such as Cu n TC (n ≥ 2) or Cu(H) m TC 2 (m ≤ 4) was less possible as it is difficult for one single TC molecule to bond two or more Cu cations [35] and such Cu/TC complexes were only formed under very acidic or alkaline condition [33]. Mitscher et al [36] reported that Cu 2+ tended to complex with the BCD ring of TC molecules (electronic supplementary material, figure S1) at pH < 7.5 with the Cu/TC molar ratio < 1.…”
Section: Adsorption Of Tetracycline On Goethite As Influenced By Molar Metal/tc Ratiosmentioning
confidence: 99%
“…[4] . Os valores obtidos de K f estiveram abaixo daqueles obtidos em literatura para OTC em solos temperados [124] , demonstrando que esta Outro fato também a ser considerado para o maior valor de K d de T1 é que a maior presença de cátions metálicos leva a uma maior interação entre a OTC e a MO por meio de pontes metálicas, pois a OTC é um forte agente quelante para cátions metálicos em meios a partir de pH em torno de 5 [66,133] .…”
Section: Sorção Solos-oxitetraciclinaunclassified